Molecular engineering enables high-performance hybrid perovskite photodetector - Peiding Liu; Xing Zhang; Bolei Zhang; Yong Wang; Wanbiao Hu; Feng Qiu (Chip)
Highly optical-absorption hybrid perovskites with upgraded stability and superior photoelectronic properties are essential for optoelectronics. However, various defects are generated by the solution-based film quality inevitably produces during the crystallization process, which leads to non-radiative recombination and interface mismatch. In this work, polyvinylpyrrolidone (PVP) molecule layer was implemented as the interfacially multifunctional layer and selective transport layer to fabricate an effective photodetector. Interfacial PVP is conductive to the bond coordination between the PVP molecule and the MAPbI3 surface, which could lower the work function of the perovskite film and effectively improve its surface morphology so as to isolate it from water and oxygen molecules. The interfacial passivation for the undercoordinated Pb2+ defects was also verified via first-principles calculations. The electron injection barrier can be regulated via interfacial molecule engineering, leading to the result that the dark current is suppressed by five orders of magnitude to 1.57 × 10−11 A, and the specific detectivity improved by about three orders of magnitude reaching 2.9 × 1012 Jones. These results provide a feasible route to fabricate highly sensitive and stable hybrid perovskite photodetectors.